Perceptions of the prehistoric in Anglo-Saxon England religion, ritual, and rulership in the landscape - Semple, Sarah 1973- (Oxford Univ. Press, 2013)
Perceptions of the Prehistoric in Anglo-Saxon England represents an unparalleled exploration of the place of prehistoric monuments in the Anglo-Saxon psyche, and examines how Anglo-Saxon communities perceived and used these monuments during the period AD 400-1100. Sarah Semple employs archaeological, historical, art historical, and literary sources to study the variety of ways in which the early medieval population of England used the prehistoric legacy in the landscape, exploring it from temporal and geographic perspectives. Key to the arguments and ideas presented is the premise that populations used these remains, intentionally and knowingly, in the articulation and manipulation of their identities: local, regional, political, and religious. They recognized them as ancient features, as human creations from a distant past. They used them as landmarks, battle sites, and estate markers, giving them new Old English names
Keywords: Geschichte 400-1100; Rezeption; Vor- und Frühgeschichte; England